(untitled) (Perner’s Contacts, 2023)
The presented article deals with the complex reconstruction and analysis of a specific traffic accident on the highway. The main goal of the analysis of the traffic accident was to determine the cause of death of the driver of the Škoda 1203. The accident occurred at night with the participation of 3 passenger cars, between which there was mutual impact contact. These mutual contacts determined the technical-logical definition of the accident scene with acceptable time intervals between individual impact contacts. The time-spatial determination of the technically acceptable interval of the course of the traffic accident made it possible to define the time available for the driver of the Škoda 1203 vehicle to perform post-accident actions. The subsequent biomechanical analysis made it possible to establish the probable mechanism of the serious injuries of the given driver.